Exploring Customer Preference to Develop an Effective Customer Relationship Management Strategy: A Case Study of Comvee, an Adaptive-Clothing Brand - Trahutama, Frederika Amelia (Integrasi Sains Media, 2024)
Comvee is a clothing brand specializing in adaptive apparel that facilitates easy and quick dressing for individuals with high mobility needs. This research aims to identify Comvee's customer preferences, explore how Comvee's Customer Relationship Management (CRM) correlates with these preferences, and provide recommendations for aligning CRM strategies with customer preferences. The study examines three dimensions of customer preference: Product Perception, Price Perception, and Promotion Perception. For CRM, the dimensions are Customer Attraction, Value Delivered to Customers, and Customer Engagement. A quantitative approach was used, with data collected via an online survey distributed to 115 respondents who follow Comvee on Instagram and TikTok. Descriptive Analysis, Spearman's Correlation Analysis, and Cross-tabulation Analysis were employed to assess the relationships between variables. The results indicate a strong positive correlation between Customer Preference and CRM, with a correlation coefficient of 0.815. Customers preferred effective promotional communication, clear product value and benefits, products meeting their needs, and prices aligning with their tolerance. Recommendations for enhancing Comvee's CRM include optimizing social media engagement tailored to the target audience, focusing on the 25-34 age group, strengthening offline presence and community building, and emphasizing product functionality, benefits, and value in promotions.